Analisis Pengaruh Waktu terhadap Kualitas VCO (Virgin Coconut Oil) Berbau Tengik dan Berbau Harum Santan dengan Metode tanpa Pemanasan - Dzakma Putri Alsa; Ghina Khairiyah; Tashania Zhahyra; Della Rosalynna Stiadi; Deffia Aryati Putri; Jon Efendi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This study aims to evaluate the effect of different settling times on the quality of Virgin Coconut Oil (VCO) produced without heating (cold process), by comparing two time variations: 3 hours and ±18 hours (variation 1) and 4 hours and ±24 hours (variation 2), through organoleptic tests (color, aroma, taste), acid value, and pH analysis. The results showed that VCO from variation 2 had better quality, with a clear color, a fresh coconut-like aroma, a pleasant taste, an acid value of 1.707 mg KOH/g, and a pH of 6.4–6.5, all of which met the quality standards of SNI 7381-2008. In contrast, variation 1 showed imperfections in oil separation due to shorter settling time, which triggered oxidation and fat hydrolysis. Thus, optimal settling time in the cold process method is a key factor in producing high-quality VCO that is free from rancid odor.